Variability of the nutritional composition of Brazilian corn ethanol coproducts for pigs (Research, Society and Development, 2021)
The grain ethanol industry has been growing in Brazil due to the availability of corn, generating great diversity and quantity of by-products for animal feed. These co-products can be ingredients for the pig industry as long as their composition is known. The objective was to reference the chemical and nutritional composition for pigs from Brazilian by-products. Determinations of dry matter (DM), mineral matter (MM), crude protein (PB), ether extract (EE), neutral detergent fiber (NDF), particle size (TP), and gross energy (EB) were carried out, digestible (ED), metabolizable (EM), liquid (EL) in addition to total lysine (LT) and digestible (LD) via prediction equations for nine corn ethanol by-products. There was a significant variation in the chemical and physical composition of the Brazilian co-products analyzed, which influenced the variability in the values of energy and lysine. The highest amplitudes of values were recorded for MS, MM, EB, LT and LD. The highest values for PB were registered in the HP-DDGS followed by the DDGs of U2 and U4, while the lowest values of MS and NDF were found in the soluble ones. The highest values of ED, EM and EL were registered in the HP-DDGS, WDG and DDGS of the U1 plant. The HP-DDGS showed the best chemical, physical and nutritional composition, suggesting greater suitability for use in pig diets.